The Asymmetric Continental Shelf Wave in Response to the Synoptic Wind Burst in a Semienclosed Double‐Shelf Basin. Issue 1 (7th January 2018) - Qu, Lixin; Lin, Xiaopei; Hetland, Robert D.; Guo, Jingsong
Abstract: The primary goal of this study is to investigate the asymmetric structure of continental shelf wave in a semienclosed double‐shelf basin, such as the Yellow Sea. Supported by in situ observations and realistic numerical simulations, it is found that in the Yellow Sea, the shelf wave response to the synoptic wind forcing does not match the mathematically symmetric solution of classic double‐shelf wave theory, but rather exhibits a westward shift. To study the formation mechanism of this asymmetric structure, an idealized model was used and two sets of experiments were conducted. The results confirm that the asymmetric structure is due to the existence of a topographic waveguide connecting both shelves. For a semienclosed basin, such as the Yellow Sea, a connection at the end of the basin eliminates the potential vorticity barrier between the two shelves and hence plays a role as a connecting waveguide for shelf waves. This waveguide enables the shelf wave to propagate from one shelf to the other shelf and produces the asymmetric response in sea level and upwind flow evolutions. Key Points: Sea level fluctuation response to wind burst is asymmetric in a double‐shelf basin, the Yellow Sea This asymmetric sea level response is due to the shelf wave propagating from the Korea side to Chinese side via topographic wave guide